Botulinum Toxin: Preparations for Clinical Use, Immunogenicity, Side Effects, and Safety Profile - Dashtipour, Khashayar; Pedouim, Farzin (Seminars in Neurology, 2016)
Botulinum toxin (BoNT) formulations are being used for a variety of medical applications. The use of BoNT preparations is continuously expanding with new formulations and indications. Of the seven antigenically distinct BoNTs, only two serotypes, type A and type B are commonly available for therapeutic use. The four available BoNT products are not equivalent and the knowledge of their formulations is crucial for product selection, avoidance of medication errors, therapeutic efficacy and safety. Generally, BoNT injection is a safe procedure when administered by an experienced injector. Side effects are always transient, and in the majority of cases they are mild and tolerable.
Keywords: AbobotulinumtoxinA; OnabotulinumtoxinA; IncobotulinumtoxinA; RimabotulinumtoxinB